PENYULUHAN DAMPAK MINYAK BEKAS PAKAI PADA IBU TP-PKK KABUPATEN SUMBAWA DALAM RANGKA PENINGKATAN PENGETAHUAN DAN SIKAP KESEHATAN - Nurlaila Agustikawati; Lina Eta Safitri; Fitri Setianingsih (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The highest contribution of rising cooking oil prices to inflation occurred in November and December 2021, namely 0.08 percent each. The consumer price index for the food sub-group, which contained cooking oil commodities, was recorded to have increased from 107.10 in September 2021 to 112.34 in March 2022 (Setiawan, 2022). This encourages consumers, namely housewives and MSMEs, to switch to using used cooking oil or using oil repeatedly. Cooking oil that is used repeatedly can cause health problems and the waste can pollute the environment. Mothers have a very important role in the household, especially managing the consumption of people at home to maintain family health. In terms of preparing food for family members, mothers need to have high knowledge about food ingredients consumed and used in cooking. One form of our concern for health academics in improving health standards is through community service programs that we carry out through outreach activities about the dangers of used oil (used cooking oil). This activity began with participant registration, where participants who came were 23 participants consisting of TP-PKK members of Sumbawa Regency. The result of this activity is increased knowledge and attitude of using used cooking oil repeatedly at the household level